Multiple tubulin forms in ciliated protozoan Tetrahymena and Paramecium species - Libusová, Lenka; Dráber, Pavel (Protoplasma, 2006)
Tetrahymena and Paramecium species are widely used representatives of the phylum Ciliata. Ciliates are particularly suitable model organisms for studying the functional heterogeneity of tubulins, since they provide a wide range of different microtubular structures in a single cell. Sequencing projects of the genomes of members of these two genera are in progress. Nearly all members of the tubulin superfamily (alpha-, beta-, gamma-, delta-, epsilon-, eta-, theta-, iota-, and kappa-tubulins) have been identified in Paramecium tetraurelia. In Tetrahymena spp., the functional consequences of different posttranslational tubulin modifications (acetylation, tyrosination and detyrosination, phosphorylation, glutamylation, and glycylation) have been studied by different approaches. These model organisms provide the opportunity to determine the function of tubulins found in ciliates, as well as in humans, but absent in some other model organisms. They also give us an opportunity to explore the mechanisms underlying microtubule diversity. Here we review current knowledge concerning the diversity of microtubular structures, tubulin genes, and posttranslational modifications in Tetrahymena and Paramecium species.
Keywords: Tubulin; cilie; financování organizované; Animals; posttranslační úpravy proteinů; Microtubules; Financing, Organized; Tetrahymena; tubulin; zvířata; Cilia; mikrotubuly; Paramecium; Protein Processing, Post-Translational